Synthetic Biology - New Interdisciplinary Science 2020
DOI: 10.5772/intechopen.86976
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Genic Male-Sterility Genes and Their Applications for Plant Heterosis via Biotechnology-based Male-sterility Systems

Abstract: In this chapter, we summarize the strategies about molecular cloning and functional confirmation of plant genic male-sterility (GMS) genes and their applications for hybrid breeding and seed production via biotechnology-based male-sterility (BMS) systems in crop plants. The main content includes four sections: (1) GMS gene cloning strategies, including forward genetic approaches (e.g., map-based cloning, T-DNA or transposon tagging, and MutMap method) and reverse genetic approaches (e.g., homology-based clonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…So far, more than 100 GMS genes have been cloned in plants, and most of them are investigated in model plants Arabidopsis and rice, while less than 20 GMS genes have been reported in maize (Wan et al ., 2019). Notably, most of the reported GMS genes are identified via the forward genetic approaches, such as map‐based cloning, T‐DNA or transposon tagging and MutMap methods (Wan and Wu, 2020), which are dependent on the existing GMS mutants. As the GMS genes often show anther‐specific or anther‐preferential expression patterns, it is reasonable to predict GMS genes by using anther transcriptomic analysis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…So far, more than 100 GMS genes have been cloned in plants, and most of them are investigated in model plants Arabidopsis and rice, while less than 20 GMS genes have been reported in maize (Wan et al ., 2019). Notably, most of the reported GMS genes are identified via the forward genetic approaches, such as map‐based cloning, T‐DNA or transposon tagging and MutMap methods (Wan and Wu, 2020), which are dependent on the existing GMS mutants. As the GMS genes often show anther‐specific or anther‐preferential expression patterns, it is reasonable to predict GMS genes by using anther transcriptomic analysis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, the proportion of tissue-specific transcribed genes in anther is the highest (6.0%) when compared with other tissues during various developmental stages (Figure S6), suggesting that maize anther transcriptome has a special content and that the GRN underlying anther development may be more complicated. Previous studies have identified a number of functional genes involved in anther development, including TF-coding genes that are crucial regulatory nodes in the networks, enzyme-coding genes that participate in lipid and carbohydrate metabolism, and transporter genes [2,5,6,7,64,65]. Additionally, several miRNAs combined with their target genes were found to have important functions in regulating the floral organ identity and the subsequent development of anther and pollen [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the 101 DEGs includes 21 key genes that are homologs of FATB, KASI, KASII, SAD, KCS, LACS, HCD, CER1, KCR, and OFADH in Arabidopsis, indicating that they are essential for anther cuticle and pollen exine biosynthesis (Figure 2; Supplemental Table 3) (Kunst and Samuels, 2009;Li-Beisson et al, 2013). Therefore, elucidating the functions of the predicted 101 novel lipid metabolic genes and confirming that they are GMS genes in maize using a reverse genetic approach will greatly improve our in-depth understanding of the molecular and biochemical networks regulating anther and pollen development in maize and other plants (Wan and Wu, 2020). This interesting work is ongoing in our lab.…”
Section: Molecular Plantmentioning
confidence: 99%